PELATIHAN ENGLISH STORY TELLING UNTUK PENINGKATAN PERSONEL SELLING PELAKU UMKM - Dewi Surani; Rini Dwi Septiyani (Jurnal Abdimas Bina Bangsa, 2022)
English training for UMKM at Rumah Kreatif BUMN Bogor – Cilegon was held by virtual learning using zoom meeting on April 29th, 2021. The aim of this training was to master public speaking with storytelling techniques that will be marketed directly by using social media. The participants were trained to describe the product that will be marketed and then tried to tell it in English. The training begins with an activity on understanding product storytelling. Participants were given examples of how to create product descriptions to be marketed through video storytelling. The material was delivered with a dialogue interactive method. In this training, the participants were asked to practice the storytelling technique one by one using their respective products. Product Storytelling training was going well and was successful for UMKM members who are currently required to use social media to improve their selling products through English storytelling